Histone deacetylase inhibition with givinostat: a multi-targeted mode of action with the potential to halt the pathological cascade of Duchenne muscular dystrophy - Aartsma-Rus, A. (Frontiers in Cell and Developmental Biology, 2025)
Muscle repair and regeneration are complex processes. In Duchenne muscular dystrophy (DMD), these processes are disrupted by the loss of functional dystrophin, a key part of the transmembrane dystrophin-associated glycoprotein complex that stabilizes myofibers, indirectly leading to progressive muscle wasting, subsequent loss of ambulation, respiratory and cardiac insufficiency, and premature death. As part of the DMD pathology, histone deacetylase (HDAC) activity is constitutively increased, leading to epigenetic changes and inhibition of muscle regeneration factors, chronic inflammation, fibrosis, and adipogenesis. HDAC inhibition has consequently been investigated as a therapeutic approach for muscular dystrophies that, significantly, works independently from specific genetic mutations, making it potentially suitable for all patients with DMD. This review discusses how HDAC inhibition addresses DMD pathophysiology in a multi-targeted mode of action and summarizes the recent evidence on the rationale for HDAC inhibition with givinostat, which is now approved by the United States Food and Drug Administration for the treatment of DMD in patients aged 6 years and older.